Negotiating paradise lost: Refugee narratives of pre-war Syria – A discursive approach to memory, metaphors and religious identifications. (October 2020) - Løland, Ingrid
How are social relations and ethno-religious identifications of pre-war Syria remembered and narrated by Syrian refugees in exile? Crossing the abyss of war, and negotiated through the shifting times and sites of forced displacement, this article addresses Syrian refugee narratives as discursive practices that attempt to reclaim an irretrievably lost terrain. The metaphor of a 'paradise lost' is an unmistakable component of the Syrian refugees' stories, illustrating multiple understandings of 'paradise' in which memories of the past gain a particularly idealized character. At the same time, however, and to some extent belying this metaphor, there are traces of tension-filled undercurrents that call for a plural reading of the past. Discussed within a theoretical framework of memory, metaphors and religious identifications, the empirical analysis highlights two narrative themes: (1) coexistence and diversity: narratives of intercultural and inter-religious relations and (2) living under authoritarian rule: narratives of fear and compliance. Leading up to the revolution and subsequent civil war, these narratives display the ambivalent ways in which Syrian refugees conceptualize the past.